Reasons for teachers’ resistance to reforms ideas about education - Torquato , Maria Socorro G.; Ghanem , Elie (Seven Editora, 2024)
This article brings evidence that supports the hypothesis that, when there is dissonance between the logic of educational reforms and teachers’ ideas about school education, consequently, there is some form of resistance to the former. Such ideas would come from the socialization of teachers, especially during the period of their basic education. This hypothesis contradicts the assertion of part of the literature about resistance, which attributes the resistance to reforms to poor teacher training. The arguments proposed here were elaborated in order to situate a research that was carried out on the ideas of teachers from São Paulo about school education. DOI:https://doi.org/10.56238/sevened2024.009-029